Inteligência coopetitiva setorial: uma proposta de modelo - Schneider, Ariane Hinça (2015)
The business environment context points at the necessity of new forms of management for the sustainable competitiveness of organizations through time. Coopetition is characterized as an alternative in the interaction of different actors, which compete and cooperate simultaneously, in the pursuit of common goals. This dual relation, within a gain-increasing perspective, converts competitors into partners and fosters competitiveness, especially that of organizations within a specific sector. The field of competitive intelligence has, in its turn, assisted organizations, individually, in the systematization of information valuable to decision-making processes, which benefits competitiveness. It follows that it is possible to combine coopetition and competitive intelligence in a systematized process of sectorial intelligence for coopetitive relations. The general aim of this study is, therefore, to put forth a model of sectorial coopetitive intelligence. The methodological outlining of the study is characterized as a mixed approach (quantitative and qualitative methods), of an applied nature, of exploratory and descriptive aims. The Coordination of the Strategic Roadmapping Project for the Future of Paraná's Industry is the selected object of investigation. Protocols have been designed to collect primary and secondary data. In the collection of the primary ata, online questionary were sent to the sectors selected for examination. A total of 149 answers to the online questionary were obtained, and interviews were performed with all embers of the technical team of the Coordination, in a total of five interviewees. After the collection, all the data were tabulated, analyzed and validated by means of focal groups with the same five members of the Coordination technical team, and interviews were performed with a representative of each of the four sectors selected, in a total of nine participants in the validation. The results allowed the systematization of a sectorial coopetitive intelligence model called ICoops. This model is characterized by five stages, namely, planning, collection, nalysis, project development, dissemination and evaluation. Each stage is detailed in inputs, activities and outputs. The results suggest that sectorial coopetition is motivated mainly by knowledge sharing, technological development, investment in R&D, innovation, chain integration and resource complementation. The importance of a neutral institution has been recognized as a facilitator and incentive to the approximation of organizations. Among the main difficulties are the financing of the projects, the adhesion of new members, the lack of tools for the analysis of information and the dissemination of the actions.